صفات المومنين في سورة ال عمران - Nurhidayah Binti Mohd Ayub; نورهداية بنت محمد أيوب (Universiti Sains Islam Malaysia, 2022)
This research on tittle " Sifat Orang Mukmin Dalam Surah Ali Imran". It is focused to the concept of Iman and all the elements accordingly. The purity character of Muslim and sign of mukmin stated in surah Ali Imran versus. This research proposed to identify the fact of Iman. Iman is an important asset in human life. In other word, the research also to know it very well based on al-Quran sources particularly of Ali Imran versus and generally in al-Quran in order to practice by society. To complete this research, used appropriates methodology as library research. Then, had been referred the references through nearby of library around the area. This research has been concluded that one of the reality of iman has been described deeply through al-Quran and Sunnah and other references. Then, it found that between mukmin there are closed of relationship. Therefore, Ali Imran versus has listed of mukmin characteristics that ways to success in world and hereafter.